(untitled) (Journal of Human Sciences, 2022)
It focuses on the implementation of major and important projects, including the investment of natural resources, such as oil, gas, minerals, airport construction contracts, infrastructure, construction, operation and transfer of ownership (BOT) contracts. Therefore, there must be complete transparency in the announcement and contracting of these projects and solving the problems resulting from them, in order to protect public money. And advancing the national economy in a successful and effective manner. On the other hand, defining the rights and obligations of investors within the territory of the investing country through organizing them within a legislative and agreement framework in an organized and accurate manner is not enough to reassure the investor contracting with the state. There must be means to protect these rights in the event of a state breach of its obligations, hence the importance of arbitration in settling these disputes from international trade contracts in general and administrative contract disputes in particular.